Examining factors influencing behavioural intention of managers in fraudulent financial reporting: Evidence from Pakistan / Riaz Ahmed - Riaz , Ahmed (2021)
The modern business world is substantially full of risks and challenges that the global crimes and illegal financial activities are growing rapidly. All the stakeholders such as the owners, shareholders, investors, and regulators have raised much concern over increasing number of corporate scandals. The growth of irregular accounting transactions, business scandals, and fraudulent financial reporting has developed a milieu of mistrust among the businesses and their stakeholders while making financial reporting decisions. It is essential to understand the fundamental factors related to unethical financial reporting intentions of corporate managers. This study aims to (1) examine the influence of managersï¿½ attitudes towards their behavior intention in fraudulent financial reporting, (2) examine the influence of subjective norms towards managersï¿½ behavior intention in fraudulent financial reporting, (3) examine the influence of perceived behavioral control towards managersï¿½ behavior intention in fraudulent financial reporting, (4) examine whether religiosity moderate the relationships between managersï¿½ attitudes, subjective norms, perceived behavioral control, and behavior intention in fraudulent financial reporting and (5) examine whether perceived organizational support (POS) moderate the relationships between managersï¿½ attitudes, subjective norms, perceived behavioral control, and behavior intention in fraudulent financial reporting. The theoretical root that framed this study is the Theory of Planned Behavior (TPB) which provides for an examination of a respondentï¿½s attitudes, subjective norms, and perceived behavioral control in the development of the intention to perform a specific behavior. The population of this study is the managerial positions especially finance and accounting managers who are working in Pakistani public and private companies listed at Karachi Stock Exchange. The sample from this population developed a suitable representation of experienced and professional managers. This study applied a quantitative research design to collect data from the respondents. A survey questionnaire was distributed among 400 respondents, out of which 229 complete and usable responses were received. These responses measured the strength of the respondentï¿½s favorable or unfavorable opinions concerning TPBï¿½s related constructs (three exogenous constructs - attitude, subjective norm, and perceived behavioral control, and the endogenous construct of intention), religiosity, and perceived organizational support. The partial least squares structural equation modelling (PLS-SEM) technique was applied to examine the proposed research framework by using Smart PLS. This study followed the two-steps analytical approach suggested by Anderson and Gerbing (1988) and Hair et al. (2005). First, a confirmatory factor analysis (CFA) was performed to test the constructs validity in the measurement model. Then structural model was assessed to examine the hypothesized the relationship between variables. The results suggest that attitude toward behavior, subjective norms, and perceived behavior control have significant influences on the behavioral intention of managers to violate IFRS to meet earnings prediction. In addition, the findings suggest that subjective norm is the strongest predictor of intention. Surprisingly, the moderation effects of religiosity and POS are found to be insignificant. The findings of this research contribute to existing fraudulent financial reporting literature by empirically proving the relationships between the elements that influence the behavioral intention of managers to commit corporate fraud. Thus, this study provides an insight for the top executives to encourage the managers on ethical decision making that may help alleviate unethical behavior as well as risks of fraud in an organization.